Digitalization and Innovation in Higher Education - Rizka Dwi Puspitasari; Nayla Rifqita (Journal of Strategy and Transformation in Educational Management, 2026)
The rapid development of digital technology has led to significant transformations in higher education, particularly in the learning process. Digital learning has become a key strategy to enhance flexibility, effectiveness, and accessibility for students. This study aims to analyze the implementation of digital learning in higher education and to identify its benefits, challenges, and impacts on learning quality. The research adopts a qualitative approach using literature review and document analysis related to policies and practices of digital learning in higher education institutions. The findings indicate that the implementation of digital learning improves students’ learning autonomy, expands access to learning resources, and encourages innovation in teaching methods. However, challenges such as limited infrastructure, readiness of human resources, and gaps in digital literacy remain significant barriers. Therefore, comprehensive development strategies, including the enhancement of digital competencies among lecturers and students as well as strong institutional policy support, are required to ensure the optimal and sustainable implementation of digital learning in higher education.